Improved Spectrophotometric Estimation of Sulphadiazine as Pure Form and in Its Pharmaceutical Preparations Via Condensation Reaction. - Azeez, Dheyaa T.; Mohammed, Salim A. (Libyan Journal of Science &Technology, 2025)
This research includes the development of a sensitive, swift and low-cost spectrophotometric procedure for estimating sulfadiazine in the form of pure substance and in its pharmaceutical dosage forms via condensation reaction. The method was involved the reaction of sulphadiazine with 4-dimethylaminobenzaldehyde in an acidic medium of HCl to produce a yellow soluble product has maximum absorption intensity at the wavelength 452 nm. The calibration graph was linear and compatible to Beer's low over the range of concentration 0.5 to 15ppm with a determination coefficient (r2= 0.9995) and molar absorptivity 2.90´104 l/mol.cm. The detection limit (DL), quantification limits (QL) and the sensitivity of Sandell were calculated and found to be 0.0543, 0.1810 µg/ml and 0.00860 μg/cm2, respectively. A relative error percentage and the relative standard deviation were calculated and found to be in the range -3.8% to 0.36% and ±0.33 to ±1.26%, respectively. The method has been successfully applied to assay sulfadiazine in burn cream and veterinary drugs (injection and powder).